(untitled) (Medical Forum Monthly, 2021)
Objective: The objective of this study to evaluate saliva biochemical composition of pregnant women and non- pregnant women in Mirpur AJK. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the department Physiology and Biochemistry Department of Mohtarma Benazir Bhutto Shaheed Medical College Mirpur AJK from March 2018 to August 2019. Materials and Methods: Total 200 anemic patients were selected male and female and 100 control healthy people were selected for the study. Lipid profile (Total cholesterol, HDL, VLDL and triglycerides) was estimated in both groups in anemic patient and control healthy people. Blood samples were collected from both groups anemic and healthy people. Samples were analyzed by Micro lab 300 for lipid profile for both groups anemic and control .Merck kits were used for analysis of lipid profile in both groups. Hematology study was conduct by used hematology analyzer. Kits of Merk Company were used for analysis. Results: The total mean cholesterol (mg) in anemic patients was 182.6 ± 29.5 while in healthy control was 193.6 ± 30.5.The mean LDL (mg) in anemic patients was 105.8 ± 15.5 while in healthy control was 118.7± 19.3. The mean HDL (mg) in anemic patients was 42.77± 8.4while in healthy control was 59.3 ± 8.1. The mean Triglycerides (mg) in anemic patients was120.2 ± 29.while in healthy control was 133.3 ± 31.2. Result showed that lipid profile is lower in anemic patient as compare to healthy control subjects .The mean Hb (g/dl) in anemic patients was8.88 ± 1.32 while in healthy control subjects was12.79 ± 1.43. The mean Serum iron (μg/dl) in anemic patients was38.32 ± 6.35while in healthy control subjects was96.15 ± 18.68. The mean TIBC (μg/dl) in anemic patients was 399.03 ± 41.48 while in healthy control subjects was282.72 ± 27.04. The mean Serum ferritin (μg/dl) in anemic patients was9.93 ± 3.8 while in healthy control subjects was49.4 ± 31.00. Conclusion: The result showed that in anemia and lipoprotein relationship exist but the type of anemia is not affect the relationship. The lipoprotein level is decreased in anemic patient as compare to control.